STRATEGI PENGEMBANGAN PRODUK TABUNGAN SANTRI BERDASARKAN ANALISIS SWOT (STUDI KASUS PADA BMT KHAIRUL IKHWAN MARTAPURA) - Septianor Nugraha; Muhammad Wahdini (Jurnal Istiqro, 2023)
The research uses qualitative and quantitative analysis techniques. Qualitative analysis is used to describe the process of activities and determine alternative company strategies, while quantitative analysis is used to identify internal and external factors. The purpose of this study was to determine internal factors, external factors, alternative strategies, and marketing strategy priorities for students' savings products at BMT Khairul Ikhwan Martapura. The results of the identification of the company's internal factors show the strengths that are currently owned by the company, namely having a ball pick-up system, giving packages/prizes, free administration fees, satisfying service and using an IT application system. While the internal factors that are the company's weaknesses, namely limited manpower or employees, taking savings once a year, lack of promotion, not yet widely known product and lack of product development to meet market demand. From the results of the identification of the company's external factors, opportunities were generated that could be utilized by the company, namely the majority of students in Martapura, high public trust in BMT Khairul Ikhwan, many people began to be interested in the sharia system, cooperated with agencies, and had laws that supported BMT. Meanwhile, the threat to companies is the decline in the ability of santri/students to save, the large number of Islamic financial institutions, the more innovative products of other competitors equipped with advanced technology, the large number of the same/similar products, and savers who are not bound by BMT membership. The priority strategies for BMT Khairul Ikhwan Martapura are maintaining trust and establishing good communication, optimizing marketing resources, improving product quality, expanding market share, looking for new tips in disseminating student savings products, BMT must optimize increasing customer loyalty, carry out various kinds of social activities in the community, and maintain human resources with the potential to provide the best service in order to face competitors.